Characterization of a Low-Molecular-Weight Glutenin Subunit Gene from Bread Wheat and the Corresponding Protein That Represents a Major Subunit of the Glutenin Polymer - Masci, Stefania (American Society of Plant Physiologists, 1998)
Both high- and low-molecular-weight glutenin subunits (LMW-GS) play the major role in determining the viscoelastic properties of wheat (Triticum aestivum L.) flour. To date there has been no clear correspondence between the amino acid sequences of LMW-GS derived from DNA sequencing and those of actual LMW-GS present in the endosperm. We have characterized a particular LMW-GS from hexaploid bread wheat, a major component of the glutenin polymer, which we call the 42K LMW-GS, and have isolated and sequenced the putative corresponding gene. Extensive amino acid sequences obtained directly for this 42K LMW-GS indicate correspondence between this protein and the putative corresponding gene. This subunit did not show a cysteine (Cys) at position 5, in contrast to what has frequently been reported for nucleotide-based sequences of LMW-GS. This Cys has been replaced by one occurring in the repeated-sequence domain, leaving the total number of Cys residues in the molecule the same as in various other LMW-GS. On the basis of the deduced amino acid sequence and literature-based assignment of disulfide linkages, a computer-generated molecular model of the 42K subunit was constructed.